UPAYA PENINGKATAN KUALITAS PEMBELAJARAN BIOLOGI MELALUI PEMBELAJARAN BERMAKNA DENGAN MENGGUNAKAN PETA KONSEP - Jailani Jailani; Almukarramah Almukarramah (Universitas Serambi Mekkah, 2020)
One of the efforts to increase instructional effectiveness is by developing a meaningful learning strategy thought using concept mapping. The instructional objectives at school are not only to increase the academic achievement but also the ability and skill of the students in order to be able to understand the process of improving knowledge, attitude to the subject which is studied, and attitude to the environment, too. The instructional strategy with concept mapping is one of the alternatives that can provide the result of all aspects that are hoped to reach the instructional objectives. The concept mapping learning strategy signifies the students reorganize the new knowledge by inserting the concept into the net hierarchically and describe their connection in a diagram and combine it into a greater knowledge structure. The organizing of conceptual understanding well will aid the meaningfulness of students learning, so, the students are easier to understand the material of the lesson being studied.